Community organizing and governance. - Ferrer, Oscar P. (Philippine Journal of Public Administration)
The Local Government Code (LGC) of 1991 pave the way for broader people's participation in local governance. It gave the local government units (LGUs) power to organize themselves to become self-reliant communities and to realize the essence of community governance. This article highlights the significance of community participation and governance in attaining genuine people-oriented development. It illustrates community governance as a critical element in effective Public Administration in contemporary period. This is shown through a analysis of selected communities where their perceptions on the role of LGUs vis-a-vis LGC are presented. There are two study areas in this article, with two case samples per area: people-initiated (Aeta and KINIPAN's case) and LGU-initiated (Balanga City and General Nakar) community organizing efforts. A cross-comparison in terms tackled to determine the general trends that can be gleaned from the cases.